2014
DOI: 10.1155/2014/530815
|View full text |Cite
|
Sign up to set email alerts
|

Mefloquine and Its Enantiomers Are Active againstMycobacterium tuberculosisIn Vitro and in Macrophages

Abstract: Objective. Tuberculosis is a serious problem of public health. The increase on the number of clinical cases of tuberculosis infected with multidrug resistant (MDR) M. tuberculosis calls for the development of novel therapy. Design. We investigated the effect of mefloquine and two enantiomers, (+)erythro-mefloquine and (+)threo-mefloquine against M. tuberculosis strains in the environment resembling the aspects of the granuloma environment and in macrophages. Results. The results suggest that mefloquine (racemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…Limited data on the in vitro activity of mefloquine against M. tuberculosis have documented MICs ranging from 8 to 16 mg/L, 18,19 and our study validates these findings. Serum levels of mefloquine range from 1 to 2 mg/L at standard dosing for malaria (Table 3), which is well below the demonstrated MICs.…”
Section: Mefloquinesupporting
confidence: 87%
See 1 more Smart Citation
“…Limited data on the in vitro activity of mefloquine against M. tuberculosis have documented MICs ranging from 8 to 16 mg/L, 18,19 and our study validates these findings. Serum levels of mefloquine range from 1 to 2 mg/L at standard dosing for malaria (Table 3), which is well below the demonstrated MICs.…”
Section: Mefloquinesupporting
confidence: 87%
“…But studies have indicated that mefloquine concentrates in macrophages to levels Cavanaugh et al DST of MDR-TB isolates JAC above the MICs. 18,20 If this finding can be substantiated, then mefloquine may have clinical utility in the treatment of drug-resistant TB, and further clinical investigation would be warranted.…”
Section: Mefloquinementioning
confidence: 99%
“…Drug repositioning or repurposing, i.e. finding new indications for existing/approved drugs, is an increasingly utilized strategy in search of novel medicines [3,4], for example antiparasitic [5,6] and antimycobacterial use of antimalarial drugs [7,8]. Repurposing of antimalarial drugs as anticancer agents is particularly interesting, since different classes of antimalarials display either direct or adjuvant activity against cancer, act as sensitivity reversers of resistant tumour cell lines, inhibitors of drug resistance development, or synergistic agents with known anticancer drugs [9e22].…”
Section: Introductionmentioning
confidence: 99%
“…Despite their structural similarity, these two quinolines possess two different antimicrobial spectra. BQ 2a is only active against mycobacteria [7,14] in the nanomolar range, while MQ 1a/1b is active against Plasmodium falciparum in the nanomolar range and Gram-positive bacteria and mycobacteria in the micromolar range (Figure 1) [9,15,16,17]. ( R , S )-BQ 2a targets very specific mycobacteria, including M. tuberculosis and M. avium [14], due to its great affinity to the mycobacteria F0F1-ATP synthase [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, some biochemical evidence has associated the antibacterial properties of MQ to its interaction with the F0F1-ATP synthase [21]. Even if MQ 1a/1b is used as racemic mixture, studies suggest this is the best activity of the enantiomer (+)-( S , R )-MQ compared to its optical antipode against P. falciparum and M. tuberculosis in vitro and M. avium in vivo [16,17,23]. However, this difference in activity is not observed against bacteria such as S. aureus , Enterococcus faecalis or Streptococcus pneumonia [9,21].…”
Section: Introductionmentioning
confidence: 99%